In order to solve this, we can subtract one equation from the other so we can cancel one of the variables and solve for it, like this:
By multiplying the second equation by 2, we get:
2×(14y + 5x) =2×248
2×14y + 2×5x = 2×248
28y + 10x = 496
By subtracting the second equation multiplied by 2 from the first one we get
As you can see, we got -20y = -240. By dividing both sides by -20, we get:
-20y = -240
-20y/-20 = -240/-20
y = 12
Then, y = 12.
By replacing 12 for y into one of the equations we can easily solve for x, like this:
8y+10x=256
8(12) + 10x = 256
96 + 10x = 256
96 - 96 + 10x = 256 - 96
10x = 160
10x/10 = 160/10
x = 16
Then x = 16
Summary:
x = 16
y = 12